Творчі та наукові здобутки Едгара Ковача у Львівській політехнічній школі - Петровська, Ю.; Кузьмич, В.; Kuzmych, V.; Petrovska, Yu. (Видавництво Львівської політехніки, 2019)
Творчість Едгара Ковача займає провідне місце в архітектурі Галичини. В умовах Львівської політехніки він проявив себе як практикуючий архітектор, реставратор, теоретик мистецтва та професійний керівник потужного Університету. Його високий фаховий рівень архітектурної графіки сприймають на європейському рівні.

The works of Edgar Kováts occupies a significant place in the architecture of Galicia. he established himself as a practicing architect, restorer, art theorist, and professional leader of a powerful university in the context of Lviv Polytechnic. His high professional level of architectural graphics is perceived at European level. This year marks the 100th anniversary of the renowned architect, graphic artist, painter, art theorist, rector of Lviv Polytechnic Edgar Kováts. His high graphic skills are driven by long hard work, and a persistent desire to create. This is a kind of “Leonardo”, which at the turn of the century showed his brilliant works, enriching the culture of architectural graphics. His architectural, painting, restoration and other works of art of the late 19th – early 20th centuries became true masterpieces of European art. Edgar Kováts genius is still incomprehensible, and his high professionalism is undeniable. The purpose of the article is to highlight the uniqueness of the architectural achievement of architect Edgar Kovach during the formation of the Lviv architectural school. Relationship between Lviv architects’ art and contemporary achievements of European graphic art of public and sacral architecture. The admiration of Edgar Kováts folk arts and crafts formed a new theory of “East Galician” artistic style, aimed at interpreting works of folk art in the Carpathian region. Integration of Lviv Architectural School into European Culture is shown. The practical experience gained in the implementation of orders under the guidance of Austrian masters, enriched the creative potential of the architect, was able to accumulate a tremendous experience of graphic practice and to reach the level of European skill. E. Kováts managed to successfully transfer him to the territory of Galicia, where he completed a number of wonderful projects
Edgar Kováts creative and scientific achievements in Lviv polytechnic schoo
Keywords: архітектурна школа; Едгар Ковач; художні дисципліни; архітектурна графіка; народне мистецтво; architectural school; Edgar Kováts; disciplines of art; architectural graphics; folk art; 76.01